Low Radar Cross-section and Low Cost Dipole Antenna Reflector - Machado, G. G.; de Melo, M. T.; Silva Filho, H. V. H.; Neto, A. G.; de Souza, T. R. (Advanced Electromagnetics, 2017)
This paper presents a method for reducing Radar CrossSection (RCS) of an increased gain metal backed dipole antenna. Numerical simulations were done and compared to a laboratory experiment. The results show that when a Perfect Electrical Conductor (PEC) is replaced by a Frequency Selective Surface (FSS), the antenna is still able to perform with the desired characteristics, but the RCS of the structure is greatly reduced out of band. The design of the FSS and the return loss, gain improvement, and RCS are presented for an antenna operating at 4.2GHz, and the results are compared with a conventional metal backed layout. Measurements show a good agreement with the simulations, and so the advantages on other structures from the reviewed literature are mentioned.